Analisis Leverage Pada PT Indofood Sukses Makmur Tbk - Nuriati Nuriati (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2020)
This study aims to determine how much leverage the research uses the ratio of debt (Debt Ratio) or Debt to Total assets by comparing total debt divided by total assets, at Pt. Indofood Sukses Makmur Tbk .. The population used in this study is the financial statements of Pt. Indofood Sukses Makmur Tbk in the form of a balance sheet (financial position) which consists of total liabilities and total assets for 24 years, starting from 1992-2018. The sample used in this study for 5 (five) years, starting from 2014–2015. The sampling technique used is purposive sampling according to Sugiyono (2012: 85). Purposive sampling is a sampling technique with certain considerations. The writer's consideration lies in the readiness of data and the use of new data (update). The data analysis technique was the one sample t-test. Based on statistical calculations, the results of the study show that the value of T = - 2.412.948 is obtained. Furthermore, this figure is compared with T table for an error level of 5% (0.05) and degrees of freedom (dk) = n-k = 5-1 = 4, then obtained T table = 2.132 then compared, then Tcount ≥ T table (-2.412,948 ≥ 02,132 so that the number shows Ha is accepted and H0 is rejected. This means that "leverage analysis on Pt.Indofood Sukses Makmur Tbk means that the average value of Debt ratio is not the same as value 35%. which is expected is good.